JESAYA Innovation for Reducing MMR and IMR in Barito Utara Regency (Case Study) - Nancy Nancy; vanny Frida; Widiantoto saputro; zhafirah yanzli anisah; achmad zainuddin; frit tarong; erna susanti (BPJS Kesehatan, 2023)
A major strategic priority of Barito Utara Regency is maternal and neonatal health issues since the maternal mortality rate (MMR) and infant mortality rate (IMR) have fluctuated with an increasing trend from 2016 to 2022. This case discusses innovation at Kandui Public Health Centre in Gunung Timang Subdistrict as the only thriving area that brought down IMR and MMR to zero for five consecutive years (2019-2023). Despite the benefits of JESAYA (Jembatan Bersalin Sayang Anak/Child-Friendly Maternity Bridge) innovation being recognised, its adoption rate by other public health centres remained low. This study aims to identify the intrinsic factors influencing the diffusion of JESAYA. To study these issues adequately, a qualitative case study with a phenomenological approach was selected using various data collection techniques, including interviews with nine research subjects, observation, and documentation. The results suggest that adopting innovation is not straightforward, and its intrinsic factors play a crucial role in its success. Additionally, it appears that the process of adopting JESAYA has a social component, which collegial interactions and discussions may facilitate.